(untitled) (Studia Prawnicze / The Legal Studies, 2007)
Prokura podlega obowiązkowemu wpisowi do rejestru przedsiębiorców prowadzonego w ramach Krajowego Rejestru Sądowego (art. 1098 § 1 k.c.). Podobnie jak to miało miejsce w przypadku wpisu do rejestru handlowego, również z wpisem do rejestru przedsiębiorców ustawodawca wiąże wiele skutków prawnych, określanych w doktrynie zasadami rejestru. Do najważniejszych z nich zalicza się zasady: 1) jawności formalnej, 2) jawności materialnej, 3) wiarygodności. Działanie tych zasad ma istotny wpływ na prawidłowość funkcjonowania prokury w obrocie gospodarczym. Dotyczy to w szczególności: 1) umożliwienia prokurentowi wykazania wobec osób trzecich swego umocowania; 2) stworzenia osobom trzecim możliwości upewnienia się, że majądo czynienia z prokurentem; 3) zapewnienia osobom trzecim, działającym w zaufaniu do zarejestrowanych danych, odpowiedniej ochrony. Argumenty te skłaniają do szerszego omówienia zasad związanych z wpisem prokury do rejestru. The article is devoted to the issues connected with an entry into the Register of procuration. Such a registration is of a declaratory character, thus it is not necessary to establish the authorization. However, its significant legał conseąuences reąuire a separate analysis. Since a datę of a disclosure in the Entrepreneurs’ Register, the procuration gains a broader effectiveness towards third parties, as it is connected with the binding presumptions of an openness (in its formal and materiał aspect) and of an authenticity of the data disclosed in the Register. The entry of procuration into the Entrepreneurs’ Register results in a protection, which shall be considered, at least, in two aspects. It gives not only a possibility of making use of an extract from the Entrepreneurs’ Register allowing to legitimize an existence of procuration (especially before courts and central govemment bodies) by its holder, but it also protects third parties, towards whom the registered entrepreneur can not ąuestion a validity of procuration entered into the Register. Furthermore, there are some benefits to an entrepreneur resulting from an entry of procuration into the Entrepreneurs’ Register. Most important of them focuses on a fact that after an expiry of a period of 16 days sińce the data (on the procuration establishment) entered into the Register have been disclosed, no one can use the ignorance of that fact as an excuse.